A New Energy Efficient and Antenna Selection Based Index Modulation Technique - Cogen, Fatih; Ozden, Burak Ahmet; Aydin, Erdogan (IEEE, 2024)
In this paper, a new multiple input multiple output technique called CIM-HQAM-SM is presented by combining the high data rate and energy-efficient communication techniques of code index modulation (CIM), spatial modulation (SM), and energy-efficient hexagonal quadrature amplitude modulation (HQAM). In the proposed system, since the incoming information bits determine the modulated symbols, the active transmit antenna indices, and the corresponding spreading code indices, the data bits are transmitted not only by the modulated symbols but also by the active antenna and spreading code indices. Therefore, the proposed system consumes less transmission power and provides better error performance compared to the SM and quadrature SM (QSM) methods in the literature, and shows similar performance with the CIM-SM system. Moreover, the proposed system is enhanced with COAS technique to improve the system performance. The performance analysis of the proposed system is performed for Rayleigh fading channels.
Keywords: Code index modulation; spatial modulation; hexagonal quadrature amplitude modulation (HQAM); MIMO systems; Computer Science; Engineering; Telecommunications